MDCT Diagnosis and Staging of Xanthogranulomatous Pyelonephritis - Stefania Tamburrini; Rosita Comune; Giulia Lassandro; Filomena Pezzullo; Carlo Liguori; Valeria Fiorini; Stefano Giusto Picchi; Marina Lugarà; Dario Del Biondo; Salvatore Masala; Fabio Tamburro; Mariano Scaglione (Diagnostics, 2023)
Background: Benign nephrectomy to treat patients with renal inflammatory disease in cases of severe urinary infection represents a diagnostic and management challenge because of significant inflammatory, fibrotic, and infectious components. Among renal inflammatory diseases, fistulization and invasiveness to adjacent structures are some of the hallmarks of xanthogranulomatous pyelonephritis (XGP). The aims of this study were as follows 1. to retrospectively determine key demographic and clinical features of XGP among benign nephrectomies; 2. to assess the CT preoperative diagnostic accuracy; and 3. to define the imaging characteristics of the CT stage. Material and Methods: A retrospective review of clinical, laboratory, and radiological features and operative methods of patients who underwent benign nephrectomy with histologically proven XGP was performed. Results: XPG was diagnosed in 18 patients over a 4-year (2018–2022) period. XGP represented 43.90% among benign nephrectomies. The mean age of the patients was 63 years, and the sex prevalence was higher in women (72.22%). Symptoms were vague and not specifically referrable to urinary tract disorders and unilateral (100%), with the left kidney affected in 61.11% of cases. Staghorn calculi and stone disease were the most common underlying cause (72.22%). All patients underwent CT. The preoperative CT imaging accuracy for renal inflammatory disease was 94.44% and indeterminate in 5.56%. A suspected diagnosis of XGP was formulated in 66.67% (12/18; 2 stage II/10 stage III), meanwhile, in 33.33% (6 patients with stage I), a non-specific diagnosis of renal inflammatory disease was formulated. CT was reported according to the Malek and Elder classification and staged in the stage I nephric form (33.33%), stage II perinephric form (11.11%), stage III paranephric form (55.56%). Conclusions: The CT diagnostic accuracy for kidney inflammatory disease was extremely high, whereas the suspected diagnosis of XGP was formulated preoperatively in only 66.67% of high-stage disease, where the hallmarks of invasiveness and fistulization of the pathology increased the diagnostic confidence.